2020
DOI: 10.3389/fmed.2020.00330
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Anxiety, and Depression in Patients With Early-Stage Mycosis Fungoides and the Effect of Oral Psoralen Plus UV-A (PUVA) Photochemotherapy on it

Abstract: Background: Little is known about psychological discomfort and quality of life (QoL) in early stage mycosis fungoides (MF) and the effect of psoralen plus UV-A (PUVA) on it. Objective: To evaluate QoL, anxiety, and depression with validated instruments in early stage MF patients and whether PUVA treatment improves it. Methods: Patients with stage IA to IIA MF were treated with PUVA twice weekly for 12-24 weeks, followed by maintenance treatment or not, in a prospective randomized clinical trial. Patients compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…It is encouraging to discover that they acknowledge the emotional influence of MF. Interestingly, previous studies have reported low anxiety levels in patients (5,18,19). However, concerns were raised regarding the adequacy of the scales used to assess anxiety in these patients, and it is possible that patients with more advanced stages indeed are more anxious.…”
Section: Discussionmentioning
confidence: 99%
“…It is encouraging to discover that they acknowledge the emotional influence of MF. Interestingly, previous studies have reported low anxiety levels in patients (5,18,19). However, concerns were raised regarding the adequacy of the scales used to assess anxiety in these patients, and it is possible that patients with more advanced stages indeed are more anxious.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of any demographic or obvious clinical differences between the objective responders and the nonresponders contributes to the strength of the data. Only one other study to date has evaluated psychological distress in relation to treatment in this population, 7 assessing the impact of PUVA. Our study adds evidence to support the benefit of other treatment modalities on mental health in this population as well as the impact of treatment on worrying.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Psoralen plus ultraviolet A photochemotherapy (PUVA) has recently been shown to improve health-related quality of life and psychological well-being in patients with early-stage MF. 7 However, only limited general psychological distress questionnaires have been used for CTCL, while no worry-specific instruments have been used.…”
Section: Introductionmentioning
confidence: 99%
“…scalp, nails, palms/soles or inverse/genital areas), arthritis, depression or systemic treatment. Adjusting the data used for the PFIS statistical analysis (as was done in a previous study for DLQI) by excluding the items with the answer “does not apply to me” (as was previously done for DLQI) 23 did not significantly change the study results (data not shown).…”
Section: Discussionmentioning
confidence: 99%